Neišleisti 1853-1854 m. Lauryno Ivinskio kalendoriai - Labanauskienė, Danutė (Knygotyra, 1997)
Famous man of Lithuanian culture of the 19th century, pedagogue, naturalist, lexicographer, and writer Laurynas Ivinskis (1810–1881) published his calendar in the Lithuanian language each year from 1846 until 1864 and again in 1878. The calendars of 1853 and 1854 were banned by Tsarist Russian censorship.Manuscripts of those Ivinskis' calendars are in the Library of the Lithuanian Academy of Sciences. They reveal the oppressive atmosphere created by Russian censorship on the educational and cultural life of Lithuania. Parts of the text were banned by censor A. Petkevičius. The correspondence between L. Ivinskis and printer A. Zavadzkis provides insights into the editor's printing business. New details of L. Ivinskis' biography are disclosed. All didactic stories and other articles that were banned in 1853-1854 survived in Ivinskis' manuscripts and were published in later editions of the calendars. One of these articles appeared in the book Pasauga (1875) by L. Ivinskis, but this book was also banned.